2006
DOI: 10.1111/j.1399-0004.2006.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of pathogenic mutations and associated polymorphisms in a cohort of 44 unrelated patients with long QT syndrome

Abstract: Long QT syndrome (LQTS) is a rare and clinically heterogeneous inherited disorder characterized by a long QT interval on the electrocardiogram, increased risk of syncope and sudden death caused by arrhythmias. This syndrome is mostly caused by mutations in genes encoding various cardiac ion channels. The clinical heterogeneity is usually attributed to variable penetrance. One of the reasons for this variability in expression could be the coexistence of common single nucleotide polymorphisms (SNPs) on LQTS-caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 76 publications
1
52
1
1
Order By: Relevance
“…Inherited loss-of-function mutations of Kv7.1 and KCNE1 are associated with long QT syndrome (LQT), in which the ventricular action potential duration is prolonged, resulting in a high risk of ventricular arrhythmias and sudden death. Eleven previously reported LQT-associated mutations (39)(40)(41)(42)(43)(44)(45)(46) affect basic residues in the PIP 2 pocket (Table S1). For these mutations, loss of VSD-PD coupling may compromise the I Ks channel function and create a substrate for cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Inherited loss-of-function mutations of Kv7.1 and KCNE1 are associated with long QT syndrome (LQT), in which the ventricular action potential duration is prolonged, resulting in a high risk of ventricular arrhythmias and sudden death. Eleven previously reported LQT-associated mutations (39)(40)(41)(42)(43)(44)(45)(46) affect basic residues in the PIP 2 pocket (Table S1). For these mutations, loss of VSD-PD coupling may compromise the I Ks channel function and create a substrate for cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The nsSNPs scores found to have functional significance by both SIFT and PolyPhen are shown bold in Tables 2 and 3. The results obtained by these programs partially concur with the experimental works reported earlier. Notably, the SNP with an id rs179489 in KCNQ1 (Splawski et al 1998), rs36210422 (Laitinen et al 2000) and rs41313074 (Splawski et al 2000) in KCNH2, rs28937316 (Splawski et al 2000), rs6791924 (Yang et al 2002) and rs28937318 (Smits et al 2002) in SCN5A, rs28933384 (Schulze-Bahr et al 1997 in KCNE1, and rs2234916 (Millat et al 2006), rs16991654 (Millat et al 2006) and rs35759083 (Millat et al 2006) in KCNE2 gene reported through experimental work were also predicted to be the deleterious mutations by the SIFT and PolyPhen programs. There are a few other mutations, which are depicted as 'Predicted in this work' in Tables 2 and 3, that have not been reported experimentally so far, but must be worked out in the future.…”
Section: Damaged Nssnp Found By the Polyphen Algorithmmentioning
confidence: 99%
“…Examples of such methods are direct sequencing, denaturing high performance liquid chromatography (DHPLC), single strand conformational polymorphism analysis (SSCP), HRM analysis, and next-generation sequencing (NGS). 3,[8][9][10][11][12] Some methods for large-scale detection of the 3 major LQTScausing gene mutations are expensive and technically timeconsuming. Since 2002, HRM analysis has represented the next generation of mutation scanning technology and offers considerable time and cost savings over those methods.…”
Section: Ong Qt Syndrome (Lqts) Is a Congenital Arrhyth-mentioning
confidence: 99%